Flow injection-Spectrophotometric Determination of Phenylephrine Hydrochloride and Amoxicillin Trihydrate in Pharmaceutical Preparations - Al-Abachi, Mouayed Q; Subhi, Sadeem (Al-Nahrain Journal of Science, 2013)
A batch and flow injection (FI) spectrophotometric methods have been developed for the determination of phenylephrine hydrochloride (PHP) and amoxicillin trihydrate (AMOX) in pharmaceutical preparations. The methods are based on coupling reaction of 2,4-dinitrophenylhydrazine (DNPH) with either PHP or AMOX in the presence of sodium hydroxide to form a red colored water-soluble products with absorption maxima at 525 and 515 nm for PHP and AMOX respectively. Optimum conditions for determining the drugs were investigated. Beer’s law were obeyed over the concentration ranges of 2-50μg/ml PHP and 1-40 μg/ml AMOX for batch method, and of 30-1000 μg/ml PHP and50-1200μg/ml AMOX for FIA method. The limits of detection were 1.044 μg/ml PHP and 0.230 μg/ml AMOX for batch method, and for FI method were 14.21 μg/ml PHP and 34.00 μg/ml AMOX. The proposed methods were applied satisfactorilyto the determination of PHP and AMOX in pharmaceutical preparations. The procedures are characterized by its simplicity, accuracy and precision. The results obtained were in good agreement with those obtained using reference standard methods at the 95% confidence level.